Anterior knee pain from the evolutionary perspective - Monk, AP; Gill, HS; Gibbons, CLMH; Price, AJ; Vollrath, F; Rees, JL; Murray, DW (Elsevier, 2021)
Background This paper describes the evolutionary changes in morphology and orientation of the PFJ using species present through our ancestry over 340 million years.